A pilot study of adolescent health literacy research in Melbourne: Implementation and reflections. (19th October 2020) - Guo, Shuaijun; Davis, Elise; Armstrong, Rebecca; Yu, Xiaoming; Naccarella, Lucio
Abstract: Issues addressed: While adolescent health literacy research has gained momentum, there is little evidence regarding its implementation and data collection in school settings. This study explored the feasibility of collecting health literacy data from Australian secondary schools and piloted three health literacy instruments. Methods: A cross‐sectional study was designed to recruit four government secondary schools in Melbourne. Active, opt‐in consent was obtained from parents and students in Years 7‐9, and an online survey was conducted. Three health literacy instruments were used: the 8‐item Health Literacy Assessment Tool (HLAT‐8), the Newest Vital Sign (NVS), and the 47‐item Health Literacy Survey (HLS‐47). Results: A total of 120 students (age 12‐15 years) were finally recruited from one school, whereas the other three schools declined due to busy educational commitment or no interest in research. Learnings and reflections on data collection included: a shared perspective of health literacy evaluation between school and researchers; the feasibility of online data collection; and the possibility of obtaining passive, opt‐out consent. About one‐quarter (23.7%‐32.2%) of students were likely to have poor health literacy. Conclusions: Although the recruitment was challenging, this pilot study indicates the feasibility of large‐scale online health literacy survey in future school‐based research. So what?: Measuring and monitoring adolescent health literacy is essential to achieve the aim of the Australian Curriculum of Health and Physical Education. More implementation research is needed with representative samples to validate health literacy instruments and examine the impact of health literacy on health promotion outcomes in Australian adolescents.